2016
DOI: 10.1186/s12971-016-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of graphic health warnings as a deterrent for smoking initiation among adolescents in selected schools in southwest Nigeria

Abstract: BackgroundThere has been a sustained increment in young people initiating smoking in low middle income countries like Nigeria. Health warnings on cigarette packages are a prominent source of health information and an effective means of communicating specific disease risks to adolescents and young adults alike. This study evaluated the perceived effectiveness of selected graphic warnings on smoking initiation amongst in-school adolescents.MethodsThis was a cross-sectional study conducted amongst secondary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Participants in this study also suggested warnings which focus on pregnant women and children, and the impact of tobacco use on these vulnerable populations, and the effects of tobacco use on personal appearance, which are themes reported elsewhere . As smoking during adulthood is most often the result of experimentation during adolescence, taking advantage of the vanity of this younger age group through depicting the appearance‐related consequences of tobacco use has been theorised to be more effective than the eventual development of chronic diseases, which feel less relevant to adolescents . Ageing skin, reduced physical fitness, oral diseases and body odour were all identified by participants in this study as potentially effective messages in reducing adolescent tobacco use.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Participants in this study also suggested warnings which focus on pregnant women and children, and the impact of tobacco use on these vulnerable populations, and the effects of tobacco use on personal appearance, which are themes reported elsewhere . As smoking during adulthood is most often the result of experimentation during adolescence, taking advantage of the vanity of this younger age group through depicting the appearance‐related consequences of tobacco use has been theorised to be more effective than the eventual development of chronic diseases, which feel less relevant to adolescents . Ageing skin, reduced physical fitness, oral diseases and body odour were all identified by participants in this study as potentially effective messages in reducing adolescent tobacco use.…”
Section: Discussionmentioning
confidence: 78%
“…[30][31][32] As smoking during adulthood is most often the result of experimentation during adolescence, taking advantage of the vanity of this younger age group through depicting the appearancerelated consequences of tobacco use has been theorised to be more effective than the eventual development of chronic diseases, which feel less relevant to adolescents. [33][34][35][36] Ageing skin, reduced physical fitness, oral diseases and body odour were all identified by participants in this study as potentially effective messages in reducing adolescent tobacco use.…”
Section: Discussionmentioning
confidence: 97%
“…Pairs of packaging for three brands were presented. Packs were either branded or plain, with identical GHWs (lung damage).Participants chose one pack (or indicated ‘no difference’) from each pair based on pack attractiveness, perceived health risks, perceptions of popular smoker attributes, and pack preference.2016 Adebiyi [32]Nigeria n = 54413–17 years44.755.398.31.7In-school surveys in two schools in a single community, with participants viewing four GHWs: smoking harming children, and causing airway cancer, stroke, and impotence.Participants indicated if each warning evoked: fear; shock, anxiety, or indifference. They also utilised a 3-point Likert scale on the effectiveness of each GHWs in preventing smoking initiation.2016 Andrews [44]USA, Spain, France n = 106613–18 years50.050.0100An online survey with participants viewing one of eight packs (four plain and four branded) with varying levels of graphicness of GHWs, depicting the risks of smoking causing mouth cancer (2 × 4 model).Participants rated using 6- and 7-point scales in response to the pack their: cigarette cravings, evoked fear (4 items), pack feelings (3 items e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies were assessed by the JBI ‘Checklist for Analytical Cross Sectional Studies’ and scored out of eight, with four or below indicating low quality, five to six as moderate quality, and seven to eight as high quality [24]. Fourteen were found to be of high quality, and two of moderate quality [30, 32]. Three studies were assessed by the JBI ‘Checklist for Randomized Controlled Trials’ and scored out of 13, with seven or below indicating low quality, eight to ten as moderate quality, and ten and above as high quality [25].…”
Section: Resultsmentioning
confidence: 99%
“…However, compliance with this directive is inconsistent [31]. Furthermore, Nigeria relies only on the mandatory text-only warning and graphics are not placed on the tobacco packs [29, 32]. …”
Section: Resultsmentioning
confidence: 99%